Two new species of Marphysa Quatrefages, 1865 (Polychaeta: Eunicida: Eunicidae) from northern coast of China and redescription for Marphysa orientalis Treadwell, 1936 - Liu, Yubin; Hutchings, Pat; Kupriyanova, Elena (Zootaxa, 2018)
Two new species of Marphysa Quatrefages, 1865 (Polychaeta: Eunicida: Eunicidae), M. bulla n. sp. and M. maxidenticulata n. sp., are described from the northern coast of China with comments on the usefulness of pectinate chaetae to separate species. A redescription of Marphysa orientalis Treadwell, 1936 originally described from China is given. The genus Marphysa is widely collected for bait for recreational fishermen and anglers in China and is also exported to Australia and Japan, yet the number of species involved or their native distribution are currently unknown. It is critical that aquaculture programs know which species they are attempting to breed and their native distributional ranges. A key to all described species of Marphysa from China, including two new species described in this paper is given.